2020
DOI: 10.1523/jneurosci.3068-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Refinement of the Axon Initial Segment in Avian Cochlear Nucleus during Development

Abstract: The axon initial segment (AIS) is involved in action potential initiation. Structural and biophysical characteristics of the AIS differ among cell types and/or brain regions, but the underlying mechanisms remain elusive. Using immunofluorescence and electrophysiological methods, combined with super-resolution imaging, we show in the developing nucleus magnocellularis of the chicken in both sexes that the AIS is refined in a tonotopic region-dependent manner. This process of AIS refinement differs among cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 65 publications
(81 reference statements)
0
24
0
Order By: Relevance
“…In vitro , elevated activity can cause the AIS of excitatory neurons to relocate distally or to decrease in length, structural changes that are usually associated with decreased functional excitability ( Grubb and Burrone, 2010 ; Evans et al, 2013 , 2015 ; Muir and Kittler, 2014 ; Chand et al, 2015 ; Horschitz et al, 2015 ; Wefelmeyer et al, 2015 ; Lezmy et al, 2017 ; Sohn et al, 2019 ). In vivo , activity-dependent structural AIS plasticity has been observed in excitatory neurons, usually induced by manipulations that are long in duration and/or involve damage to peripheral sensory organs ( Kuba et al, 2010 ; Gutzmann et al, 2014 ; Akter et al, 2020 ; Pan-Vazquez et al, 2020 ; but see Jamann et al, 2021 ). But is AIS plasticity a prerogative of excitatory neurons, or is it also included in the plasticity toolkit of inhibitory cells?…”
Section: Introductionmentioning
confidence: 99%
“…In vitro , elevated activity can cause the AIS of excitatory neurons to relocate distally or to decrease in length, structural changes that are usually associated with decreased functional excitability ( Grubb and Burrone, 2010 ; Evans et al, 2013 , 2015 ; Muir and Kittler, 2014 ; Chand et al, 2015 ; Horschitz et al, 2015 ; Wefelmeyer et al, 2015 ; Lezmy et al, 2017 ; Sohn et al, 2019 ). In vivo , activity-dependent structural AIS plasticity has been observed in excitatory neurons, usually induced by manipulations that are long in duration and/or involve damage to peripheral sensory organs ( Kuba et al, 2010 ; Gutzmann et al, 2014 ; Akter et al, 2020 ; Pan-Vazquez et al, 2020 ; but see Jamann et al, 2021 ). But is AIS plasticity a prerogative of excitatory neurons, or is it also included in the plasticity toolkit of inhibitory cells?…”
Section: Introductionmentioning
confidence: 99%
“…Thus, formin inhibition-mediated actin modifications seem to play only a minor role on AIS length, due to cisternal organelle alterations, previously shown to play a role in AIS length plasticity [27]. Moreover, actin rings do not change during AIS developmental reorganization and shortening [68]. In this sense, mDia1 modulates actin-independent mechanisms, such as the spine density recovery, after Aβ peptide treatment, by an actin-binding-deficient K994A mDia1 mutant [67].…”
Section: Discussionmentioning
confidence: 86%
“…Physiological recordings also showed that these cells become more excitable [65]. The same research team recently reported that the regulation of cytoskeletal reorganization and sodium channel enrichment in the AIS differs depending on tonotopy (the spatial arrangement of sound frequency processing in the brain), but acts synergistically in the auditory nucleus [66]. These results indicate that neurons adapt to presynaptic activity and maintain neural circuit homeostasis by altering the properties of the AIS.…”
Section: Activity-responding Plasticity Of Ais In Development and Disease Modelsmentioning
confidence: 88%